Validitas dan Reliabilitas Alat Ukur Grit pada Mahasiswa di Indonesia - Lie Fun Fun; Ni Luh Ayu Vivekananda; Hera Lestari Mikarsa; Dian Kemala Putri (Humanitas (Jurnal Psikologi), 2024)
Measuring persistence or grit among university students in Indonesia is crucial, given the unique characteristics of the Indonesian context compared to Western countries. Indonesian researchers have predominantly utilized Duckworth's grit scale, which consists of two dimensions. This study aims to develop a grit measurement tool for Indonesian university students by adding a third dimension, independence, and to conduct a psychometric evaluation of the instrument. The grit construct was redefined based on three new dimensions, followed by measurements and analyses including content validity testing, readability testing, item discrimination analysis, reliability testing, and confirmatory analysis. The results showed a Cronbach's Alpha coefficient of 0.896 and a McDonald's Omega coefficient of 0.898. The standardized loading factor for items ranged from 0.608 to 0.816. Fit indices results were as follows: CFI 0.928; TLI 0.906; RMSEA 0.08; SRMR 0.043. The analysis demonstrated that the grit measurement tool has strong reliability coefficients and fits well in confirmatory analysis, indicating its validity as a 12-item instrument.